Harry Potter And The Chamber Of secrets - "Rowling, J.K" (Bloomsbury: London, 2014)
"'There is a plot, Harry Potter. A plot to make most terrible things happen at Hogwarts School of Witchcraft and Wizardry this year.'" Harry Potter's summer has included the worst birthday ever, doomy warnings from a house-elf called Dobby, and rescue from the Dursleys by his friend Ron Weasley in a magical flying car! Back at Hogwarts School of Witchcraft and Wizardry for his second year, Harry hears strange whispers echo through empty corridors - and then the attacks start. Students are found as though turned to stone
Keywords: Fantasy Good and evil Fiction